Urgensi Mahkamah Konstitusi dalam Proses Pemberhentian Presiden - Riri Nazriyah (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The existence of Constitution Court as the pioneer of constitution in Indonesia must be warmiy responded, because through this board it will be found the solution from the jurisdictive aspect when the institutional conflict of arise-between House of Representatives  and President which start from the House of Representatives' ideas thatPresident or the vice President has broken the iaw.